A transformation-grammar-based methodology for the adaptation of existing housetypes: the case of the ‘rabo-de-bacalhau’ - Eloy, S. (2016)
The research presented here aims to develop a methodology for rehabilitating the existing hous-ing stock to meet the new needs of dwellers in the current information society and the conse-quent need to integrate information, communication and automation technology into living areas. This article focuses on the use of a transformation grammar in the rehabilitation methodology as a tool for identifying and encoding the principles and rules behind the adaptation of existing hous-es, and on space syntax as a tool for evaluating the spatial properties of the proposed designs, both in the final layout and during the transformation.